The Politics of Food and Food Security during Indonesia’s Old Order (1945-1965) - Nawiyanto Nawiyanto (Universitas Gadjah Mada, 2013)
The early decades of Indonesian independence have often been described as a time of economic hardship. Food crises appeared to illustrate the absence of a strong state creating prosperity for the Indonesian people. By examining food-related policies on both the production and the consumption side, this article seeks to offer a more balanced view of the actual role of the state in achieving food self-suffciency and food security. I argue that there was a strong belief during the Old Order period that the state should play an important role in the food sector rather than letting the market mechanism determine. Various policies were executed by the government in order to increase food production and improve distribution. They were brought in practice in the feld and clearly indicate the active role that the state assumed in managing foodstuffs and food suffciency issues. The fact that food crises persisted, even later contributing to the regime change in the mid-1960s, was apparently not due to the absence of the state in the food sector, but rather to the failure of the state to overcome the hurdles of rapid population growth increasing the need for food as well as the failure to establish the political stability required for an effective and sustainable implementation of food policies.